2014
DOI: 10.1002/art.38899
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Snail Regulates Tumor Necrosis Factor α–Mediated Synovial Fibroblast Activation in the Rheumatoid Joint

Abstract: Objective. The transcription factor Snail is involved in various biologic functions. We hypothesized that this molecule regulates tumor necrosis factor ␣ (TNF␣)-mediated synovial fibroblast activation in the rheumatoid joint. The aim of this study was to examine the role of Snail in the expression of cadherin-11 (Cad-11) and myofibroblast markers, interleukin-6 (IL-6) production, and the invasive ability of cells.Methods. Synovium samples were obtained from patients with rheumatoid arthritis (RA) and from rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 46 publications
(60 reference statements)
2
50
0
Order By: Relevance
“…21,22,24,27 In a recent study, Snail overexpression was shown to increase cytokine expression and invasiveness of rat synovial cells, resulting in the exacerbation of CIA. 35 In this study, we highlight the direct implication of Snail1 that acts as a key effector of ECM degradation in arthritic FLS by promoting invadosome formation. Snail was specifically associated with the FLS subpopulation responsible for active matrix degradation and overexpressed in synovial membranes of CIA joints.…”
Section: Synoviocytes Reactivate Snail To Gain Their Invadosome-formimentioning
confidence: 83%
See 1 more Smart Citation
“…21,22,24,27 In a recent study, Snail overexpression was shown to increase cytokine expression and invasiveness of rat synovial cells, resulting in the exacerbation of CIA. 35 In this study, we highlight the direct implication of Snail1 that acts as a key effector of ECM degradation in arthritic FLS by promoting invadosome formation. Snail was specifically associated with the FLS subpopulation responsible for active matrix degradation and overexpressed in synovial membranes of CIA joints.…”
Section: Synoviocytes Reactivate Snail To Gain Their Invadosome-formimentioning
confidence: 83%
“…32e34 In addition, a recent study indicates that Snail is overexpressed in synovium and cell lines from RA patients. 35 In light of the above findings, we hypothesized that fibroblast-like synovial cells use components or pathways of the EMT program to promote invadosome formation, leading to arthritis progression toward a more destructive phenotype. Data shown herein provide evidence that the Snail transcriptional regulator is essential for ECM degradation by human and rat synovial cells and for cartilage degradation in a CIA model.…”
mentioning
confidence: 99%
“…To induce CAIA, male 8‐week‐old DBA/1J mice received IP injections of a 5‐clone monoclonal antibody cocktail (Chondrex) on day 0, followed by IP injections of lipopolysaccharide on day 3. Synovial tissue from mice with CIA was treated with collagenase, and isolated SFs were cultured continuously until confluence was reached, with cells from passages 4–7 being used in further experiments .…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant lentiviral vectors, LVshTLR4, LVMyD88, LVshLuc, and LVGFP were produced by transient transfection of 293T cells with pLKO.1-shTLR4, pLKO.1-shMyD88, pLKO.1-shLuc, and pWPT respectively, along with the packaging plasmid psPAX2 and the envelope plasmid pMD2G, as previously described29. The viral titers were determined by using cell viability assay with A549 cells to calculate relative infection unit (RIU) based on the protocol of the National RNAi Core Facility29. On the basis of qRT-PCR analysis, we chose pLKO.1-shTLR4#2 and pLKO.1-shMyD88#2 plasmids (TRCN0000065786 and TRCN0000077234) to generate lentiviral vectors that encoded TLR4 and MyD88 shRNA.…”
Section: Methodsmentioning
confidence: 99%
“…To produce TLR4- or MyD88- knocked down stable transfectants, mouse bladder carcinoma MBT2 cells were transduced with LVshTLR4 or LVshMyD88 for 48 h, respectively, in the presence of 8 μg/ml polybrene (Sigma-Aldrich, St. Louis, MO), and the cells were then incubated with puromycin (2 μg/ml) for 2 weeks. Control transfectants were obtained by transduction with LVshLuc, followed by puromycin selection29.…”
Section: Methodsmentioning
confidence: 99%